PENERAPAN TERAPI KELOMPOK TERAPEUTIK DALAM PENINGKATAN PENCAPAIAN TUGAS PERKEMBANGAN INDUSTRIPADA ANAK USIA SEKOLAH - Susanti, Amelia; Yani S. Hamid, Achir (JURNAL KEPERAWATAN BINA SEHAT, 2016)
School-age children are the future generation of the nation. It is important to pay attention to their growth and development. Children’s growth are including motoric, cognitive, language, moral, personality, spiritual, emotional, and psychosocial aspects which can be stimulated using Therapeutic Group Theraphy (TKT). The purpose of this scientific paper was to elaborate the application of TKT in facilitating the achievement of industry developments task of school-age children. TKT was applied to school age children living with their families of selected community area. The Interpersonal theory of Peplau and Erikson were used as an integrated approach. It showed that TKT has increased all aspects of children’s abilities in motoric, cognitive, language, moral, personality, spiritual, emotional, and psychosocial, and also school age children industry abilities. School’s TKT was recommended to be applied in public health service system by integrating the mental health nursing services to school age children as well as by involving health cadre to optimize the school-age children industry developments sustainability.Keyword : School age children; Development; Peplau’s Interpersonal Relationship model, therapeutic group therapy